COMPREHENSIVE ASSESSMENT OF THE QUALITY OF CHILDREN’S FISH CUTLETS OF INCREASED BIOLOGICAL VALUE - Дітріх, Ірина (SWorldJournal, 2024)
The presented work proves the feasibility of modifying the traditional recipe for amateur fish cutlets by completely replacing the main fish raw material with cod fillet with the addition of spinach puree and completely replacing the auxiliary raw materia